The Equitable Inclusion of Women in Higher Education: Some Consequences for Teaching - Litner, Bluma; Rossiter, Amy; Taylor, Marilyn (Canadian Journal of Education/Revue canadienne de l'éducation, 1992)
Although admission of women to higher education has increased, equitable inclusion of women in the academy has not kept pace. Women often experience marginality in the classroom because they may have different styles of learning and because women’s experiences are not represented in mainstream knowledge. We suggest a narrative, inductive teaching strategy that deliberately acknowl- edges women’s differences and that will contribute to knowledge. This strategy requires teaching practices aimed at (1) establishing an affirming student/teacher relationship, (2) facilitating relationships among students, (3) enabling students to articulate their knowledge and experience, and (4) helping students to engage meaningfully with course content. This approach raises new difficulties for teach- ers, difficulties to be overcome in pursuing the equitable inclusion of women in higher education. Bien que de plus en plus de femmes poursuivent des études supérieures, l’inclu- sion équitable des femmes dans les corps professoraux laisse à désirer. La marginalité dont font l’expérience les femmes dans les salles de cours tient peut- être au fait qu’elles ont des styles d’apprentissage différents et que les expérien- ces des femmes ne sont pas représentées dans les connaissances courantes. Nous proposons une stratégie pédagogique narrative et inductive qui reconnaît délibéré- ment les différences des femmes et qui contribuera à l’évolution des connaissan- ces. Cette stratégie exige des méthodes d’enseignement qui visent (1) à établir une relation manifeste entre l’étudiant et le professeur, (2) à faciliter les relations entre les étudiants, (3) à permettre aux étudiants d’articuler leurs connaissances et leurs expériences et (4) à aider les étudiants à s’engager d’une manière féconde vis-à-vis de la matière du cours. Cette approche pose de nouvelles difficultés aux professeurs, difficultés qui seront surmontées par l’inclusion équitable des femmes dans l’enseignement supérieur.